2015
DOI: 10.3389/fnbeh.2015.00264
|View full text |Cite
|
Sign up to set email alerts
|

Everyday executive functions in Down syndrome from early childhood to young adulthood: evidence for both unique and shared characteristics compared to youth with sex chromosome trisomy (XXX and XXY)

Abstract: Executive functions (EF) are thought to be impaired in Down syndrome (DS) and sex chromosome trisomy (Klinefelter and Trisomy X syndromes; +1X). However, the syndromic specificity and developmental trajectories associated with EF difficulties in these groups are poorly understood. The current investigation (a) compared everyday EF difficulties in youth with DS, +1X, and typical development (TD); and (b) examined relations between age and EF difficulties in these two groups and a TD control group cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

15
69
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 46 publications
15
69
2
1
Order By: Relevance
“…This fits with reports of increased experiences of stress and anxiety during social interactions, both in adults and children with 47,XXY (van Rijn, Stockmann et al, ; van Rijn, Swaab, Aleman, & Kahn, ). Such deviations in the generation and processing of emotional responses fit with reports increased risk for compromised emotion regulation abilities in individuals with 47,XXY (Lee et al, ). Emotion regulation has been defined as the “processes that are responsible for the monitoring, evaluating, and modifying of emotional reactions in the service of achieving goals for well‐being” (Thompson, ).…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…This fits with reports of increased experiences of stress and anxiety during social interactions, both in adults and children with 47,XXY (van Rijn, Stockmann et al, ; van Rijn, Swaab, Aleman, & Kahn, ). Such deviations in the generation and processing of emotional responses fit with reports increased risk for compromised emotion regulation abilities in individuals with 47,XXY (Lee et al, ). Emotion regulation has been defined as the “processes that are responsible for the monitoring, evaluating, and modifying of emotional reactions in the service of achieving goals for well‐being” (Thompson, ).…”
Section: Introductionsupporting
confidence: 79%
“…It is important to study this as it may help in explaining the reported lower quality of life, which includes academic and employment success (Herlihy et al, ). Of specific interest are the reported emotion regulation problems (Lee et al, ), as well as atypical emotion reactivity and emotion experience, as described below. Psychophysiological studies using skin conductance measures have revealed that 47,XXY adults may have a tendency to respond with increased arousal towards socioemotional cues (van Rijn, Barendse, van Goozen, & Swaab, ), and may have difficulties identifying and labeling experienced emotions (van Rijn, Barendse et al, ; van Rijn, Swaab, Aleman, & Kahn, ).…”
Section: Introductionmentioning
confidence: 99%
“…; Lee et al . , ) and strengths in Emotional Control and Organization of Materials (Daunhauer et al . ; Lee et al .…”
Section: Introductionmentioning
confidence: 99%
“…; Lee et al . , ). In addition, parents, but not teachers, reported difficulties on the Inhibit domain (Daunhauer et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation